An urban transportation problem solved by parallel programming with hyper-heuristics. Issue 11 (2nd November 2019) - Rodriguez, Diego A.; Oteiza, Paola P.; Brignole, Nélida B.
ABSTRACT: An innovative optimization strategy by means of hyper-heuristics is proposed. It consists of a parallel combination of three metaheuristics. In view of the need both to escape from local optima and to achieve high diversity, the algorithm cooperatively combines simulated annealing with genetic algorithms and ant colony optimization. A location routing problem (LRP), which aims at the design of transport networks, was adopted for the performance evaluation of the proposed algorithm. Information exchanges took place effectively between the metaheuristics and speeded up the search process. Moreover, the parallel implementation was useful since it allowed several metaheuristics to run simultaneously, thus achieving a significant reduction in the computational time. The algorithmic efficiency and effectiveness were ratified for a medium-sized city. The proposed optimization algorithm not only accelerated computations, but also helped to improve solution quality.